Bacterial contribution to salted anchovy (Engraulis anchoita Hubbs & Marinni, 1935) ripening process - Czerner, Marina (2013)
The bacterial populations of the salted anchovy ripening process and its potential role on the development of the typical sensory characteristics of this product were studied. Salted anchovy samples were taken during the ripening process and submitted to microbiological analyses in order to monitor the evolution of bacterial groups. According to the results obtained, the ripening process would be dominated by moderate halophilic bacteria. Moreover, many of the isolated strains showed proteolytic, lipolytic and TMAO reductase activities. All this activities would contribute to the development of typical flavour of this product and to the increase of total volatile basis observed during ripening.